PENGARUH KINERJA KEUANGAN INTERNAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Ardi Nupi Hasyim, Muhamad; Adam, Arfian (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
One important element in assessing a company is how investors believe that it will benefit from the company it is investing in. If the company succeeds in posting a large profit rate, it will motivate investors to invest in stocks, so that stock prices and stock demand will increase. This research is conducted by survey method to 50 manufacturing companies that have done the stock emission on Indonesia Stock Exchange. Technique of data collecting is done by indirect communication technique through instrument in the form of documentation study. This research was conducted from November 2016 and ended in November 2017. Data processing technique is done by Descriptive Analysis and Inferential Analysis that is Correlation Analysis and Regression with approach of analysis of variance (ANOVA). The results showed that: (1) The company's internal financial performance proportioned by its own return on equity (ROE) shows good condition, with an average of 12.17% per company, standard deviation of 14.24%; (2) Company Value measured by: (a) EMV (Equity Market Value) which is the product of P (Closing Price) x Qshares (Number of shares outstanding); (b) The book value of total debt (Debt); and (c) The book value of total assets (EBV), indicates good conditions, ie average 33.16%, standard deviation of 12.7%; (3) This hypothesis test shows ttable equal to 2,356 <tcount 5,402 (tcount> ttable) means that company's internal financial performance proportioned by return on equity (ROE) have positive and significant effect to firm value 37,8% although low but quite meaningful. The researcher suggested to pay attention to factors such as investment policy and dividend policy, because it is strongly believed to affect the increase of stock price, therefore it is proven that firm value to firm's internal financial performance proportioned by return on equity ROE) have a positive and significant effect.